2020
DOI: 10.1101/2020.03.10.980417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid growth and fusion of protocells in surface-adhered membrane networks

Abstract: Elevated temperatures might have promoted the nucleation, growth and replication of protocells on the early Earth. Recent reports have shown evidence that moderately high temperatures not only permit protocell assembly at the origin of life, but could have actively supported it. Here we show the fast nucleation and growth of vesicular compartments from autonomously formed lipid networks on solid surfaces, induced by a moderate increase in temperature. Branches of the networks, initially consisting of self-asse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The protocell networks can be formed from membranes consisting of phospholipids only, or from mixtures of phospholipids and fatty acids [ 35 ]. The networks have been shown to encapsulate water soluble compounds, even RNA and DNA [ 35 , 36 , 37 ]. Especially RNA has been a molecule of interest in origin of life studies, as it can act uniquely both as a genetic information carrier and an enzyme analog, catalyzing its own replication [ 38 ].…”
Section: Biomembrane Transformations On Solid Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocell networks can be formed from membranes consisting of phospholipids only, or from mixtures of phospholipids and fatty acids [ 35 ]. The networks have been shown to encapsulate water soluble compounds, even RNA and DNA [ 35 , 36 , 37 ]. Especially RNA has been a molecule of interest in origin of life studies, as it can act uniquely both as a genetic information carrier and an enzyme analog, catalyzing its own replication [ 38 ].…”
Section: Biomembrane Transformations On Solid Surfacesmentioning
confidence: 99%
“…The ability of model protocells to encapsulate and maintain RNA has therefore been widely investigated. The surface-adhered compartments can grow rapidly and fuse with merging of contents [ 36 ], passively replicate by transporting material through the nanotubes [ 39 ], divide, migrate, and re-attach to a surface in remote locations [ 33 ]. The protocell networks can also grow in groups in a colony-like manner, where the membranes of the individual compartments are in physical contact with each other [ 35 , 37 ].…”
Section: Biomembrane Transformations On Solid Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…2m, inset) where some of them coalesce upon physical contact. A recent study has reported on the merging of lipid vesicles if they are in close proximity in a locally heated zone 46 . Note that in order to elevate the temperature locally under avoidance of strong convection, we used an optical fiber and IR-B radiation (1470 nm, cf.…”
Section: Temperature-enhanced Formationmentioning
confidence: 99%
“…An optical fiber coupled to an IR-B laser (cf. S3) was assembled to locally increase the temperature in the sample 46,59 . A semiconductor diode laser (HHF-1470-6-95, λ = 1470 nm , Seminex), driven with an 8 A power source (4308 Laser Source, Arroyo Instruments) was used in combination with an 0.22 NA multimode optical fiber with 50 µm core diameter (Ocean Optics).…”
Section: Local Heatingmentioning
confidence: 99%